REVIEW DAN REDESIGN UNIT FILTRASI PENGOLAHAN AIR MINUM PADA PT KRAKATAU TIRTA INDUSTRI CILEGON - Pramudita, Anindya
The community needs for clean water continues to rise with the increasing number of people in Indonesia. Because the need for clean water continues to increase, it is necessary to increase the capacity of water treatment to meet those needs. The water treatment process most commonly used is the process of coagulation-flocculation, sedimentation, and filtration. The focus of this study is to evaluate the existing condition of the filter unit in a Water Treatment Plant (WTP) in PT Krakatau Tirta Industri Cilegon and redesigning for uprating activities and improving the performance of the unit. The water intake rate at the WTP in PT Krakatau Tirta Industri Cilegon is set at 5400 m3/hour and it is desired to be increased to 7200 m3/hour. Based on the evaluation, the filter in PT Krakatau Tirta Industri should be able to treat water with the planned water intake rate, which is 7200 m3/hour. However, at the time of the performance test, the filters are not able to treat all of the water when the rate exceeds 5400 m3/hour. Other than that, the filter backwash system does not meet the standards for the flow rate can not be controlled. Thus it is necessary to upgrade the filter. The improvements planned consists of adding an air scour system to the backwash system, replacement of the filter media, construction of floodgates for backwash and inlet filters, as well as adding filter-to-waste pipe. After calculating and redesigning, we acquired an air scour system with a total of 52 distribution pipe in each filter cell, replacement of media with sand media depth of 15 cm and anthracite media depth of 45 cm, the construction of floodgates to backwash with the dimensions of 2 m x 4,8 m, construction the floodgates for the filter inlet with the dimensions of 0,9 m x 2 m, and change the filter drain pipe with a filter-to-waste pipe with a diameter of 10 inches. The cost required for the construction of the filter is Rp. 7,708,750,000.00.